Benchmarks for ethically credible partnerships between industry and academic health centers: beyond disclosure of financial conflicts of interest. Issue 1 (14th December 2015) - Meslin, Eric M.; Rager, Joshua B.; Schwartz, Peter H.; Quaid, Kimberly A.; Gaffney, Margaret M.; Duke, Jon; Tierney, William M.
Abstract: Relationships between industry and university‐based researchers have been commonplace for decades and have received notable attention concerning the conflicts of interest these relationships may harbor. While new efforts are being made to update conflict of interest policies and make industry relationships with academia more transparent, the development of broader institutional partnerships between industry and academic health centers challenges the efficacy of current policy to effectively manage these innovative partnerships. In this paper, we argue that existing strategies to reduce conflicts of interest are not sufficient to address the emerging models of industry‐academic partnerships because they focus too narrowly on financial matters and are not comprehensive enough to mitigate all ethical risk. Moreover, conflict‐of‐interest strategies are not designed to promote best practices nor the scientific and social benefits of academic‐industry collaboration. We propose a framework of principles and benchmarks for "ethically credible partnerships" between industry and academic health centers and describe how this framework may provide a practical and comprehensive approach for designing and evaluating such partnerships.